GAMBARAN POLA MAKAN PENDERITA GASTRITIS DI WILAYAH KERJA PUSKESMASKAMPAR KIRI HULU KECAMATAN KAMPAR KIRI HULU KABUPATEN KAMPAR RIAU TAHUN 2012 - Sulastri .; Mhd.Arifin Siregar; Albiner Siagian (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2012)
Gastritis is disorder of health that appear caused by wrong food consumption pattern. Usually, gastritis was happen to whoses haven’t a food a regular food consumption pattern until excited production or mucous acid. This research is a descriptive study using cross-sectional design. The aim of the research was to know the description of food consumption pattern among gastritis patients. The sample is all gastritis patient was visiting puskesmas Kampar Kiri Hulu for December 2011-January 2012 amounting to 53 people. The result of research is showed 37,7% gastritis patient have a good quantity of food and 62,3% less food quantity. 17% gastritis patients where eat with right food wich be not increase gastritis and 83% not match, temporary that 28,3% gastritis patient eat with regular schedule and 71,7% unreguler. Seldom relapse frequency with good food quantity in average 24,2% and 75,8% often relapse 30%  gastritis patient increased seldom relapse with less food quantity and 70% gastritis patient increased often relapse. Gastritis patient eat right food with seldom relapse frequency 100% and for variety food which unright gastritis that seldom 31,8% and 68,3% often. For regular eat that schedule can increase seldom gastritis relapse is 100% where as fo unreguler eat schedule can increase seldom gastritis relapse 36,8% and 62,2% is often. It is suggested for public health to increase the healthy service given the information about a right food consumption pattern unreguler must to tose their bad habit it to decrease the suffer of gastritis and ensure for gastritis sufferer to eat gradually. Keyword : food consumption pattern, gastritis patient